Do Poor Countries Really Need More IT? - Eden, Maya (Published by Oxford University Press on behalf of the World Bank, 2021)
Productivity differences across countries are often attributed to differences in technological capabilities. This paper asks whether there are systematic cross-country differences in the adoption of information technologies (IT). We document a positive correlation between IT use and income, which weakens over time. However, given that IT use is an endogenous outcome of both technological capabilities and the abundance of complementary factors of production, it tends to over-state the degree of cross-country differences in technology. We propose two novel calibration approaches to address this problem. After accounting for endogenous differences in industrial composition, we find that there is no systematic relationship between income and IT capabilities.